Efisiensi Realisasi Anggaran Belanja Dan Kinerja Keuangan Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Pematang Siantar - Yuni Tirtasari Siallagan; Kusmilawaty Kusmilawaty (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to analyze the efficiency of budget realization and financial performance at the personnel and Human Resource Development Agency of Pematang Siantar. The data used in this study is secondary data pbtained from the BKPSDM budget realization report data analysis the data used is quantitative analysis by calculating the efficiency ratio and growth ratio of budget realization in 2020-2022. The results of the study show that the performance of the budget realization Office of the personnel and Human Resources Development Agency of Pematang Siantar from 2020-2022 can be seen from the analysis of the spending efficiency ratio with an average of 87.30% which reflects a fairly efficient, where the realization of spending is smaller than the budget. Then the analysis of spending variants Bkpsdm Pematang Siantar as a whole for 3 years showed good financial performance. Where from 2020-2022 Bkpsdm Pematang Siantar uses less than the budgeted amount.